Pengaruh Latihan Single-Arm Push Pass Dengan Single-Leg Standing Push Pass Terhadap Peningkatan Power Lengan - Saputra, Oki Pratama; Sutisna, Nana; Sugiawardana, Ruli; Erlina, Terra (Universitas Galuh, 2024)
Arm power is the discussion and also the dependent variable that will be revealed here. The method used is pre-experimental pretest-posttest group design. The location used for research is SMK Komputama Majenang, Cilacap Regency. The subjects used were a group of 30 men, meaning that all students as volleyball players were involved in this research. Two hand medicine ball put is used as a measuring tool. The analysis used was the SPSS series 24 application. Research results: The single-arm push pass exercise had a very good effect on improving eye and hand coordination in students at Komputama Majenang Vocational School, Cilacap Regency. The single-leg standing push pass exercise has a very good effect on improving eye and hand coordination in students at Komputama Majenang Vocational School, Cilacap Regency. There is a good difference between the single-arm push pass exercise and the single-leg standing push pass in positive changes for eye and hand coordination in students at Komputama Majenang Vocational School, Cilacap Regency. The recommendation from the research results is that carrying out exercises or doing arm power training at upper intermediate to advanced levels requires a variety of movements that lead to arm power because there are many other forms of exercise apart from the single-arm push pass and the single-leg standing push pass.Explosive otot lengan adalah pembahasan dan sekaligus variabel terikat yang akan diungkapkan di sini. Metode yang dipakai yaitu pre-experimental pretest-postest group design. Lokasi yang dijadikan penelitian yaitu SMK Komputama Majenang Kabupaten Cilacap. Subjek yang dipakai yaitu kelompok putra 30 orang, artinya seluruh siswa sebagai pemain bolavoli terlibat dalam penelitian ini. Tes melempar bola medicine dengan ke-dua lengan digunakan sebagai alat ukur. Analisis menggunakan aplikasi SPSS seri 24. Hasil penelitian: Latihan single-arm push pass berpengaruh sangat baik pada peningkatan koordinasi mata dan tangan pada siswa SMK Komputama Majenang Kabupaten Cilacap. Latihan single-leg standing push pass berpengaruh sangat baik pada peningkatan koordinasi mata dan tangan pada siswa SMK Komputama Majenang Kabupaten Cilacap. Terlihat perbedaan yang baik antara latihan single-arm push pass dengan single-leg standing push pass pada perubahan positif untuk koordinasi mata dan tangan pada siswa SMK Komputama Majenang Kabupaten Cilacap. Rekomendasi hasil penelitian bahwa melakukan latihan ataupun dalam melakukan pelatihan power lengan pada tingkat menengah atas sampai mahir diperlukan berbagai macam variasi gerakan yang mengarah kepada power lengan karena bentuk latihan masih banyak selain single-arm push pass dengan single-leg standing push pass.